2023
DOI: 10.3390/v15071589
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hTIM-1 and Envelope Protein Is Important for JEV Infection

Abstract: Japanese encephalitis virus (JEV), a mosquito-borne zoonotic virus, is one of the most important causes of human viral encephalitis. JEV relies on various attachment or entry co-factors to enter host cells. Among these co-factors, hTIM-1 has been identified as an attachment factor to promote JEV infection through interacting with phosphatidylserine (PS) on the viral envelope. However, the reasons why JEV prefers to use hTIM-1 over other PS binding receptors are unknown. Here, we demonstrated that hTIM-1 can di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The identification of host and viral factors involved in JEV entry has been an active area of scientific investigation in the literature. Many different molecules have been demonstrated to interact with JEV on the cell surface, and several studies have identified potential receptors such as heat shock protein, glucose-regulated protein 78 (GRP78), C-type lectin member 5A (CLEC5A), T-cell immunoglobulin and mucin domain 1 (TIM-1), dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), vimentin, laminin receptor, and CD4 in different cell types [ 10 , 19 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Drug Developmentmentioning
confidence: 99%
“…The identification of host and viral factors involved in JEV entry has been an active area of scientific investigation in the literature. Many different molecules have been demonstrated to interact with JEV on the cell surface, and several studies have identified potential receptors such as heat shock protein, glucose-regulated protein 78 (GRP78), C-type lectin member 5A (CLEC5A), T-cell immunoglobulin and mucin domain 1 (TIM-1), dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), vimentin, laminin receptor, and CD4 in different cell types [ 10 , 19 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Drug Developmentmentioning
confidence: 99%
“…Liang et al show that hTIM-1 protein can directly interact with Japanese encephalitis virus (JEV) E protein and mediates JEV infection and that this interaction was found to be on specific binding sites between ND114115 in the hTIM-1 IgV domain and K38 of the E protein [ 20 ].…”
mentioning
confidence: 99%